Case series of mucormycosis occurring in patients of COVID-19 - Patel, Drashti J.; Patel, Paras G.; Patel, Purvi P.; Sapariya, BrijeshKumar; Parmar, Moxa B.; Diwanji, Nehal S. (International Journal of Research in Medical Sciences, 2021)
Mucormycosis is an umbrella term used for diseases caused by many non-septate filamentous fungal species which is caused by sub-phylum Mucormycotina. It is an acute opportunistic and aggressive fulminant invasive infection that can occur in immunocompromised patients, such as uncontrolled diabetes, renal failure, organ transplant, long-term corticosteroid and immunosuppressive therapy, AIDS, malignancy and corona virus disease 2019 (COVID 19) infections. Mucormycosis is now third most common invasive mycoses after candidiasis and aspergillosis. The COVID-19 infection is characterised by wide range of disease patterns, ranging from mild to life-threatening pneumonia. Many bacterial and fungal co-infections may exist and may be associated with preexisting morbidity or may develop as a hospital-acquired infection such as ventilator-associated pneumonia. Extensive use of corticosteroids and broad-spectrum antibiotics lead to exacerbation of preexisting disease. The aim of this study is to identify the risk factors along with high index of suspicion, early diagnosis and aggressive management of mucormycosis.